Discussion on the structure and function of seeds to Cerasus discoidea. Issue 3 (April 2020) - Nan, Cheng-Hui; Xue, Xiao-Ming; Xie, Chun-Ping; Yi, Xian-Gui; Wang, Xian-Rong; Yan, Yi-Han
Abstract: Through morphological anatomy, viability measurement, seed germination and seedling growth observation, it was found that there was a ring band structure between the brown seed coat and embryo of Cerasusdiscoidea, which was the residual endosperm of Cerasus, and the seeds of Cerasus are composed of seed coat, remaining endosperm and embryo. The remaining endosperm consists of two parts: the endosperm sheath and the endosperm ring. Remaining endosperm is beneficial to the maintenance of seeds viability and the protection of seeds embryo germination and growth.